Processing technology of aluminum alloy and aluminum alloy profile
Through high-temperature asynchronous rolling on a differential rolling mill, multi-directional forging, gradient aging and hot-pressing electromagnetic bending processes, the problems of coarse grains and uneven structure of aluminum alloy profiles have been solved, and the processing of high-performance aluminum alloy profiles has been achieved, which is suitable for aerospace, automotive, construction and other fields.
Patent Information
- Application Number
- CN202510756409.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2045-06-09
AI Technical Summary
In traditional aluminum alloy profile processing technology, the cast structure is difficult to crush, the grains are coarse and the structure is uneven, resulting in poor overall performance, limiting its application in fields with stringent performance requirements.
Differential rolling mills are used for high-temperature asynchronous rolling, combined with multi-directional forging and gradient aging treatment, and coordinated with hot pressing and electromagnetic bending processes. Shear force is used to refine grains and increase dislocation density. Multi-directional forging is used to change the strain direction and eliminate anisotropy. At the same time, specific alloy elements such as Zr and Ti are used to form nano-precipitates and optimize the organizational structure.
Significantly improve the comprehensive performance of aluminum alloy profiles, including strength, plasticity, toughness and corrosion resistance, expand their application range, and meet the forming requirements of complex structural parts.
Smart Images

Figure CN120700339A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal manufacturing, in particular to a processing technology for aluminum alloy and aluminum alloy profiles. Background Art
[0002] Aluminum alloy profiles are aluminum-based alloy materials processed into specific geometric shapes. Due to their lightweight, high strength, and corrosion resistance, they are widely used in a wide range of fields, including aerospace, automotive, and construction. Traditional aluminum alloy profile processing techniques often rely on synchronous rolling. During the rolling process, the as-cast structure is difficult to effectively break up, resulting in coarse grains and uneven structure. This leads to poor overall performance and significant anisotropy, limiting their application in demanding applications.
[0003] In the comparative document (CN102634705B), by heating medium- and high-strength aluminum alloy to 490°C, extruding under specific mold temperature, extrusion speed and other conditions, and using water mist or air cooling quenching processing methods, the problem of traditional processes relying on special equipment for quenching treatment has been solved to a certain extent, and aluminum alloy profiles with high tensile strength and complex cross-sections can be produced.
[0004] However, this method has shortcomings in improving the uniformity and anisotropy of the aluminum alloy profile structure. It does not effectively control the refinement of the structure and the increase of dislocation density during the rolling process. It cannot generate shear force like the different rotation speeds of the upper and lower rollers of the differential rolling mill to break up coarse structures, refine grains, and increase dislocation density. It also does not homogenize the structure and eliminate anisotropy by changing the strain direction multiple times through multi-directional forging, which limits the comprehensive performance and application range of the profile. Summary of the Invention
[0005] In order to solve the above technical problems, the present invention provides a processing technology for aluminum alloy and aluminum alloy profiles, which is used to solve the problems raised in the background technology.
[0006] An aluminum alloy comprises the following components by mass percentage: 4.0-5.0% Zn, 1.2-1.8% Mg, 0.1-0.3% Cu, 0.08-0.12% Zr, 0.02-0.06% Ti, 0.25% Fe, and the balance is Al.
[0007] A processing technology for aluminum alloy profiles comprises the following steps:
[0008] Melting and Casting S1: Alloy elements containing Zn 4.0-5.0%, Mg 1.2-1.8%, Cu 0.1-0.3%, Zr 0.08-0.12%, Ti 0.02-0.06%, and Fe ≤ 0.25% and pure aluminum are added to a melting furnace and melted at 700-750°C to form a melt. An inert gas is introduced or a refining agent is added to refine the melt to remove gas and inclusions. The melt is then transferred to a casting device and cooled at a cooling rate of 5-15°C / s using a semi-continuous or continuous casting method to produce an ingot or billet.
[0009] High-temperature asynchronous rolling S2: using a differential rolling mill, upper roll speed 20-25rpm, lower roll speed 25-30rpm, and lower roll speed ratio 1:1.0-1.2, rolling temperature 480-500℃, total deformation 60-70%, and multi-directional forging immediately after rolling, strain path change ≥3 times, single deformation 10-15%;
[0010] Gradient aging treatment S3: The first stage adopts solution treatment at 475℃×1h, water quenching to room temperature, and the second stage adopts double-stage aging at 120℃×8h+180℃×2h, with a heating rate of ≤5℃ / min;
[0011] Hot pressing electromagnetic bending S4: the mold is preheated to 300-350℃, the bending rate is 1.0-1.2m / min, and the axial pressure of 80-100MPa and the alternating magnetic field of 0.8-1.2T are applied simultaneously. The magnetic field frequency is dynamically adjusted according to f=8×σ, where σ is the real-time compressive stress;
[0012] Surface treatment S5: Anodizing, electrophoretic coating or powder spraying are performed on the formed profile.
[0013] Preferably, the core temperature of the rolled plate is fed back in real time through infrared temperature measurement, and the roller speed is dynamically adjusted to make the temperature fluctuation ≤±5°C.
[0014] Preferably, the bending portion is subjected to local micro-arc oxidation treatment, wherein the micro-arc oxidation treatment uses an electrolyte containing 25 g / L Na2Sio3+15 g / L SiC nanoparticles, a voltage of 500 V, and a time of 6-8 min.
[0015] Preferably, in the second stage of the S2 gradient aging treatment, the heating rate from 120°C to 180°C is 3-5°C / min, and a pulsed magnetic field with a frequency of 50 Hz and a magnetic field strength of 0.5-0.8T is applied during the heating process.
[0016] Preferably, in the multi-directional forging process of S1, the strain path changes 4-6 times, the single deformation is controlled at 12-15%, and the angle between two adjacent forging directions is 90°±5°.
[0017] Preferably, the material is in a dynamic recrystallization temperature window during the bending process, and the product of the bending rate and the axial pressure does not exceed 80% of the material yield strength, wherein the mold preheating temperature and the alternating magnetic field intensity in S3 satisfy B=0.003×T+0.2, and B is the magnetic field intensity / T, and T is the mold preheating temperature / °C.
[0018] Preferably, the flow rate of the inert gas during the refining process is controlled to be 5-10m 3 / h, refining time is 15-25min.
[0019] Preferably, the rolling force applied to the rolled piece during the rolling process is 1000-1500 kN, and an emulsion is used for cooling and lubrication during the rolling process, with the concentration of the emulsion controlled at 3%-5%.
[0020] Preferably, the product model, batch and other identification information are engraved on the surface of the profile, the laser engraving power is 10-20W, and the engraving speed is 50-100mm / s.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. During operation, the differential rolling mill's upper and lower rollers rotate at different speeds, generating shear forces that break up coarse microstructures, refine grains, and increase dislocation density. Rolling at 480-500°C reduces deformation resistance, promotes dynamic recrystallization, and maintains processability. A total deformation of 60-70% further enhances performance. Post-rolling multidirectional forging repeatedly changes strain direction, breaking up grains, homogenizing the microstructure, and eliminating anisotropy, thereby improving the overall performance and application range of aluminum alloy profiles.
[0023] 2. In use, the present invention uses a solution treatment at 475°C for 1 hour to form a supersaturated solid solution, which is then water quenched to maintain the state. A two-stage aging process at 120°C for 8 hours and 180°C for 2 hours is used. The low temperature generates the GP zone to enhance strength, while the high temperature transforms the GP zone, synergistically balancing strength and toughness. A heating rate of ≤5°C / min ensures uniform precipitation of the strengthening phase, avoiding internal stress. Compared with traditional aging, this improves the comprehensive mechanical properties and service performance of the profile.
[0024] 3. During use, the present invention preheats the mold at 300-350°C and the bending rate at 1.0-1.2 m / min to ensure uniform plastic flow. The axial pressure of 80-100 MPa suppresses defects and improves the molding quality. The 0.8-1.2 T alternating magnetic field adjusts the frequency according to the real-time compressive stress, reduces deformation resistance, refines grains, improves structure and performance, and enhances fatigue resistance and corrosion resistance to meet the molding requirements of complex structural parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a bar chart comparing salt spray corrosion resistance time of the present invention;
[0026] Figure 2 This is a bar chart comparing the shear strength of this hair;
[0027] Figure 3 It is a columnar comparison chart of the minimum bending radius of the present invention;
[0028] Figure 4 It is a schematic diagram of the overall step flow structure of the present invention;
[0029] Figure 5 It is a father-son schematic diagram of a specific embodiment of the present invention. DETAILED DESCRIPTION
[0030] The following embodiments of the present invention are described in further detail with reference to the accompanying drawings and examples. The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0031] An aluminum alloy comprises the following components by mass percentage: 4.0-5.0% Zn, 1.2-1.8% Mg, 0.1-0.3% Cu, 0.08-0.12% Zr, 0.02-0.06% Ti, 0.25% Fe, and the balance is Al.
[0032] Among them, in the component system of the above-mentioned aluminum alloy, zinc (Zn) is the main strengthening element, which forms a strengthening phase during solid solution strengthening and aging, significantly improving the strength of the alloy. Magnesium (Mg) works synergistically with zinc to form a Mg-Zn strengthening phase, which not only enhances the strength of the alloy but also improves its plasticity and toughness. The addition of copper (Cu) can further improve the aging hardening effect of the alloy and enhance its heat resistance. Zirconium (Zr) and titanium (Ti) are mainly used to refine the grains, inhibit grain growth by forming dispersed compounds, and improve the comprehensive properties of the alloy. Iron (Fe) is an impurity element and its content needs to be strictly controlled to ≤0.25%, because excessive iron will form coarse intermetallic compounds, reducing the plasticity and corrosion resistance of the alloy.
[0033] The wide alternating lamellar structure of dynamically recrystallized grains and subgrains in aluminum alloys has an impact on their performance. The lamellar structure, with a single-layer width of 50-200 μm, gives the alloy anisotropy. When subjected to stress, the lamellar structure can effectively hinder dislocation movement, thereby improving the strength and hardness of the alloy. The subgrain boundary density reaches 3-5 / μm. The large number of subgrain boundaries increases the resistance to dislocation movement, further strengthening the alloy. At the same time, this structure can also improve the alloy's processing performance. During hot working, the lamellar structure is conducive to uniform deformation and reduces processing defects.
[0034] In addition, the uniform distribution of (Zr, Ti) nano-precipitates within the crystal is the key factor in improving the performance of the alloy. These nano-precipitates have a particle size of 20-40 nm and a density of ≥8×1020 pcs / m 3 They are evenly dispersed in the matrix, and effectively inhibit dislocation movement and grain growth by pinning dislocations and grain boundaries. During the service of the alloy, the nano-precipitated phase can stabilize the alloy's organizational structure, maintain the alloy's strength and hardness, and at the same time improve the alloy's fatigue resistance and corrosion resistance.
[0035] A processing technology for aluminum alloy profiles comprises the following steps:
[0036] Melting and Casting S1: Alloy elements containing Zn 4.0-5.0%, Mg 1.2-1.8%, Cu 0.1-0.3%, Zr 0.08-0.12%, Ti 0.02-0.06%, and Fe ≤ 0.25% and pure aluminum are added to a melting furnace and melted at 700-750°C to form a melt. An inert gas is introduced or a refining agent is added to refine the melt to remove gas and inclusions. The melt is then transferred to a casting device and cooled at a cooling rate of 5-15°C / s using a semi-continuous or continuous casting method to produce an ingot or billet.
[0037] High-temperature asynchronous rolling S2: using a differential rolling mill, upper roll speed 20-25rpm, lower roll speed 25-30rpm, and lower roll speed ratio 1:1.0-1.2, rolling temperature 480-500℃, total deformation 60-70%, and multi-directional forging immediately after rolling, strain path change ≥3 times, single deformation 10-15%;
[0038] Among them, high-temperature asynchronous rolling is the key starting step in aluminum alloy profile processing. Its process parameters are set based on the scientific principles of material processing. A differential rolling mill is used, with the upper roll speed at 20-25rpm and the lower roll speed at 25-30rpm. The lower roll speed ratio is controlled at 1:1.0-1.2. This speed difference breaks the uniform pattern of metal deformation in traditional synchronous rolling. During asynchronous rolling, the speed difference between the upper and lower rolls and the aluminum alloy billet causes the billet to be subjected to shear force in the rolling direction. This shear force promotes the plastic flow of the metal, breaks up the coarse cast structure, achieves grain refinement, and increases the dislocation density inside the metal, creating conditions for subsequent recrystallization and structural optimization.
[0039] The rolling temperature is set at 480-500°C, which is within the hot working temperature range of aluminum alloys. Within this temperature range, aluminum alloys have good plasticity and can achieve large deformations with relatively low rolling forces. Higher temperatures reduce the metal's resistance to deformation, reduce roll wear, and promote dynamic recrystallization. Dynamic recrystallization eliminates work hardening, ensuring that the aluminum alloy maintains good plasticity and processing properties even under large deformations. The total deformation is controlled at 60-70%, which further refines the grains, increases the alloy density, and enhances the mechanical properties of the profile.
[0040] Multi-directional forging is carried out immediately after rolling, with the strain path changing ≥3 times and a single deformation of 10-15%. This step deepens the effect of high-temperature asynchronous rolling. Multi-directional forging changes the strain direction multiple times, causing the aluminum alloy to withstand compression and shear in different directions. This complex deformation method further breaks up coarse grains and makes the structure more uniform. The strains in different directions interact with each other, promoting dislocation interaction and reorganization to form a more stable substructure. Multiple strain path changes can eliminate the anisotropy that may be caused by rolling, balance the performance of aluminum alloy profiles in all directions, and improve the comprehensive performance and application range of the profiles.
[0041] Gradient aging treatment S3: The first stage adopts solution treatment at 475℃×1h, water quenching to room temperature, and the second stage adopts double-stage aging at 120℃×8h+180℃×2h, with a heating rate of ≤5℃ / min;
[0042] The first stage uses a 475°C × 1h solution treatment, which is close to the solvus temperature of aluminum alloy. At this temperature, the alloy strengthening phase is fully dissolved in the matrix to form a uniform supersaturated solid solution. The 1h solution treatment time ensures that the strengthening phase is fully dissolved while preventing grain growth caused by excessive time. The rapid cooling method of water quenching to room temperature inhibits the precipitation of the strengthening phase and retains the supersaturated solid solution state, creating conditions for subsequent aging strengthening.
[0043] The second stage adopts a two-stage aging process of 120℃×8h+180℃×2h, with a heating rate of ≤5℃ / min. The two-stage aging process is designed to achieve the precipitation of strengthening phases of different sizes and types. The first stage 120℃×8h low-temperature aging promotes the formation of small GP zones. GP zones are enriched areas of solute atoms in the matrix, with a size of about a few nanometers. They can hinder dislocation movement, produce aging hardening effects, and improve alloy strength. The second stage 180℃×2h high-temperature aging promotes the transformation of GP zones into larger θ ‘’ Phase and θ ’ Phase, further strengthens the alloy, and synergizes with the GP zone formed by low-temperature aging to achieve a balance between strength and toughness. The slow heating rate (≤5℃ / min) avoids uneven organization and internal stress caused by rapid temperature change, ensuring uniform precipitation of strengthening phase during aging. Compared with the traditional single-stage aging process, the gradient aging treatment controls the temperature and time at different stages, regulates the precipitation process and size distribution of the strengthening phase, so that the aluminum alloy profile has both high strength and good plasticity and toughness, thereby improving the comprehensive mechanical properties and service performance of the profile.
[0044] Hot pressing electromagnetic bending S4: the mold is preheated to 300-350℃, the bending rate is 1.0-1.2m / min, and the axial pressure of 80-100MPa and the alternating magnetic field of 0.8-1.2T are applied simultaneously. The magnetic field frequency is dynamically adjusted according to f=8×σ, where σ is the real-time compressive stress.
[0045] The bending rate is set at 1.0-1.2m / min, which allows the profile to have sufficient time for plastic flow during the deformation process, avoiding local stress concentration and uneven deformation caused by excessive deformation. At the same time, it is conducive to controlling the profile forming specifications, ensuring that the bending angle and shape meet the design requirements. Simultaneously, 80-100MPa axial pressure is applied. This force acts along the axis of the profile during the bending process, suppressing thinning and wrinkling at the bend of the profile, making the metal flow in the bending area more uniform, and improving the profile forming quality and size scale.
[0046] Then, an alternating magnetic field of 0.8-1.2T is applied, and the magnetic field frequency is dynamically adjusted according to f=8×σ (σ is the real-time compressive stress). This is the innovation of hot-pressing electromagnetic bending. The alternating magnetic field acts on electrons and atoms in the aluminum alloy through the Lorentz force, changing the dislocation movement and diffusion behavior inside the metal. The dynamically adjusted magnetic field frequency is associated with the real-time compressive stress, so that the magnetic field can be adaptively adjusted according to the stress state during the profile bending process. In areas with large compressive stress, the magnetic field frequency is correspondingly increased, which enhances the effect of the magnetic field on the metal, promotes dislocation slip and reorganization, reduces the metal deformation resistance, and facilitates plastic deformation of the profile. At the same time, the alternating magnetic field can refine the grains, improve the profile structure and properties, and improve the profile fatigue resistance and corrosion resistance. Compared with the traditional bending process, the hot-pressing electromagnetic bending process improves the forming quality and performance of aluminum alloy profiles through the synergistic effect of mold preheating, moderate bending rate, axial pressure and dynamically adjusted alternating magnetic field, providing technical support for the application of aluminum alloy profiles in complex structural parts.
[0047] Surface treatment S5: Anodizing, electrophoretic coating or powder spraying are performed on the formed profile.
[0048] Example 1: conventional materials + conventional process;
[0049] Material composition: Zn4.5%, Mg1.4%, Cu0.2%, Fe0.2%, and the balance is Al (in accordance with the standard composition of 7N01 aluminum alloy in GB / T3190-2020).
[0050] Processing technology:
[0051] Hot rolling: constant speed rolling mill (roller speed 20 rpm), rolling temperature 400 ° C, total deformation 60%;
[0052] Aging treatment: T6 single-stage aging (120℃×24h);
[0053] Bending: Bending at room temperature, speed 0.5m / min, without auxiliary pressure or magnetic field;
[0054] Performance data:
[0055] Fatigue strength: 245MPa (ASTME466, R=-1,107 Second cycle);
[0056] Shear strength: 235MPa (GB / T6396);
[0057] Bending performance: minimum bending radius 1.5 times the wall thickness, springback angle 3.5°;
[0058] Microstructure: Equiaxed crystals (average grain size 50 μm), no lamellar subgrains;
[0059] The coarse equiaxed crystals and lack of lamellar subgrain structure make the material have less resistance to dislocation movement when subjected to stress and the grain boundary strengthening effect is weak. This structure is difficult to effectively hinder crack propagation. Under stress conditions such as fatigue and shear, the material performance is poor. It is also not conducive to the control of profile shape accuracy during forming processes such as bending.
[0060] Specific aluminum alloy performance parameters are shown in Table 1:
[0061] Table 1: Performance of aluminum alloy profiles made of conventional materials and constant speed rolling process
[0062]
[0063] Example 2: the above aluminum alloy material + conventional process;
[0064] Material composition: Zn4.8%, Mg1.6%, Cu0.25%, Zr0.1%, Ti0.04%, Fe≤0.15%;
[0065] Processing technology: the same as the conventional process of Example 1;
[0066] Performance data:
[0067] Fatigue strength: 280 MPa (14% higher than Example 1);
[0068] Shear strength: 265 MPa (up 13%);
[0069] Precipitation phase characteristics: Al3(Zr,Ti) phase density 5×10 20 pcs / m 3 , particle size 35 nm (TEM analysis);
[0070] Defects: Due to insufficient conventional rolling temperature, the lamellar structure is not formed and the crack growth rate is only reduced by 8%;
[0071] Specific aluminum alloy performance parameters are shown in Table 2:
[0072] Table 2: Performance parameters of aluminum alloy profiles using new materials combined with conventional processes
[0073]
[0074] Example 3: Conventional materials + above process
[0075] Material composition: the same as the conventional composition of 7N01 in Example 1;
[0076] Processing technology:
[0077] High-temperature asynchronous rolling: upper roll 20 rpm / lower roll 25 rpm, 480°C, total deformation 65%; further multi-directional forging was performed 4 times (strain path 90°);
[0078] Gradient aging: 475℃×1h solution + 120℃×8h-180℃×2h (heating rate 4℃ / min);
[0079] Hot pressing electromagnetic bending: mold temperature 320℃, magnetic field strength 1.0T, speed 1.0m / min;
[0080] Performance data:
[0081] Fatigue strength: 295MPa (120% increase over the control ratio);
[0082] Microstructure: Lamellar subgrains are formed locally (coverage 40%), and the grain size varies significantly (10-80 μm);
[0083] Bending limit: minimum radius 1.0t (limited by the plasticity of the material itself);
[0084] Specific aluminum alloy performance parameters are shown in Table 3:
[0085] Table 3: Performance comparison of aluminum alloy profiles using conventional materials and new processing technology
[0086]
[0087]
[0088] Example 4: the above materials + the above process
[0089] Material composition: Zn4.8%, Mg1.6%, Cu0.25%, Zr0.1%, Ti0.04%, Fe≤0.15%;
[0090] Processing technology:
[0091] High temperature asynchronous rolling:
[0092] Differential speed rolling mill (upper 20 rpm / lower 24 rpm), rolling at 485°C, further infrared temperature measurement and dynamic temperature control (±3°C);
[0093] Multi-directional forging 5 times (strain path 90°±3°, single deformation 14%);
[0094] Gradient aging + magnetic field coupling:
[0095] Solution treatment at 475°C for 1 h was followed by further water quenching;
[0096] Two-stage aging: 120°C × 8h followed by 180°C × 2h (heating rate 4°C / min + 50Hz / 0.7T pulse magnetic field);
[0097] Hot pressing electromagnetic bending:
[0098] Mold temperature 340°C (magnetic field B = 0.003 × 340 + 0.2 = 1.22 T);
[0099] Speed 1.1m / min, axial pressure 90MPa (satisfying 1.1×90=99MPa<σ_s×0.8=125MPa);
[0100] Local micro-arc oxidation after bending (SiC composite layer, thickness 25μm);
[0101] Performance data:
[0102] Fatigue strength: 335MPa (137% increase over the control ratio);
[0103] Shear strength: 320MPa (GB / T6396);
[0104] Bending accuracy: 90° bending angle deviation ≤ 0.3°, minimum radius 0.8t;
[0105] Microscopic features:
[0106] EBSD showed that the width of a single layer of the lamellar structure was 150 μm, and the subgrain boundary density was 4.5 / μm;
[0107] TEM shows that the density of Al3(Zr,Ti) precipitation phase is 9.2×10 20 pcs / m 3 , particle size 28nm;
[0108] Specific aluminum alloy performance parameters are shown in Table 4:
[0109] Table 4: Comprehensive performance data of aluminum alloy profiles under the synergy of new materials and innovative processes
[0110]
[0111] The above examples compare different material compositions and processing technology combinations to explore their effects on the performance of aluminum alloy profiles, which are summarized as follows:
[0112] Adding elements such as Zr and Ti to the basic aluminum alloy composition to form a uniformly distributed Al3(Zr,Ti) nano-precipitated phase can significantly improve the alloy properties. For example, compared with Example 1, under the same conventional processing technology, the fatigue strength of Example 2 is increased by 14%, the shear strength is increased by 13%, and the salt spray corrosion resistance time is extended from 500h to 800h due to the addition of Zr and Ti elements to the material, which proves the positive effect of alloying elements on improving the strength, corrosion resistance and other properties of the alloy;
[0113] Example 3 uses a high-temperature asynchronous rolling and multi-directional forging process. Compared with the conventional hot rolling process of Example 1, although the material composition is the same, the fatigue strength is improved by 120%, the salt spray corrosion resistance time is increased from 500h to 1200h, and a layered subgrain structure is locally formed, indicating that this process can refine the grains and improve the overall performance of the alloy. The gradient aging treatment controls the precipitation of strengthening phases through different stage temperatures and times to achieve a balance between strength and toughness. Compared with traditional single-stage aging, it can make the aluminum alloy profile have higher strength and good plasticity and toughness.
[0114] The fourth embodiment adopts a hot pressing electromagnetic bending process. Under the synergistic effect of mold preheating, moderate bending rate, axial pressure and dynamically adjusted alternating magnetic field, compared with the room temperature bending in the first embodiment, its 90° bending angle deviation is ≤ 0.3° and the minimum radius reaches 0.8t, which significantly improves the forming accuracy and quality. It also has a positive effect on improving the fatigue resistance and corrosion resistance of the profile.
[0115] Example 4 combines new material composition with innovative processing technology to achieve the best performance improvement effect. Its fatigue strength reaches 335 MPa, which is 137% higher than that of Example 1. The shear strength reaches 320 MPa and the salt spray corrosion resistance time is up to 3000 h. It forms an ideal wide layered alternating structure of dynamically recrystallized grains and subgrains. The density and particle size of the Al3 (Zr, Ti) precipitation phase also reach a relatively optimal state, fully reflecting the synergistic effect of material composition optimization and processing technology innovation.
[0116] In summary, optimizing the composition of aluminum alloy materials and combining them with innovative processing techniques such as high-temperature asynchronous rolling, multi-directional forging, gradient aging treatment, hot pressing and electromagnetic bending, especially effectively combining the two, can significantly improve the comprehensive performance of aluminum alloy profiles, such as strength, plasticity, toughness, corrosion resistance, and forming accuracy, providing strong support for the application of aluminum alloy profiles in complex structural parts.
[0117] In the present invention's research on aluminum alloys and aluminum alloy profiles, relevant performance data charts were generated to comprehensively explore the effects of different material compositions and processing technology combinations on the performance of aluminum alloy profiles.
[0118] The following is a bar chart comparing the salt spray corrosion resistance time ( Figure 1), shear strength bar chart comparison ( Figure 2 ) and the minimum bending radius column comparison chart ( Figure 3 ) data changes in a progressive analysis to clearly present the mechanism of action and synergistic effect of various factors on the performance of aluminum alloy profiles.
[0119] In the research of aluminum alloy profiles involved in the present invention, salt spray corrosion resistance time is a key indicator to measure its corrosion resistance. Figure 1 ) data, the salt spray corrosion resistance time of Example 1 is 500h, which is increased to 800h in Example 2, further increased to 1200h in Example 3, and reached 3000h in Example 4. This series of data changes shows a clear progressive improvement trend;
[0120] Adding elements such as Zr and Ti to the basic aluminum alloy composition to form a uniformly distributed Al3 (Zr, Ti) nano-precipitated phase has a positive effect on improving corrosion resistance. For example, compared with Example 1, the salt spray corrosion resistance time of Example 2 is extended from 500h to 800h. At the same time, the use of innovative processing technologies such as high-temperature asynchronous rolling, multi-directional forging, and gradient aging treatment can further refine the grains and improve the alloy structure, thereby significantly improving the corrosion resistance. Compared with Example 1, the salt spray corrosion resistance time of Example 3 is increased to 1200h. Example 4 combines new material components with innovative processing technologies, especially hot pressing and electromagnetic bending processes, to achieve the best corrosion resistance of aluminum alloy profiles, with a salt spray corrosion resistance time of up to 3000h. This shows that the synergistic effect of optimizing the aluminum alloy material composition and innovative processing technology can effectively extend the salt spray corrosion resistance time of aluminum alloy profiles and significantly improve their corrosion resistance.
[0121] Among them, shear strength is an important parameter for evaluating the mechanical properties of aluminum alloy profiles. Observe the shear strength column comparison chart ( Figure 2 ), the shear strength of Example 1 is 235 MPa, Example 2 is increased to 265 MPa, Example 4 reaches 320 MPa, and the shear strength of Example 3 is 300 MPa. The data show a progressive trend of gradual increase;
[0122] Adding alloying elements such as Zr and Ti can form a strengthening phase, hinder dislocation movement, and thus improve the shear strength of the alloy. Compared with Example 1 under the same conventional process, Example 2 has a 13% increase in shear strength due to the addition of Zr and Ti elements. Innovative processing techniques, such as high-temperature asynchronous rolling, multi-directional forging, and gradient aging treatment, further enhance the strength of the alloy by refining the grains and optimizing the organizational structure. After using these innovative processes, Example 3 has a shear strength higher than that of Example 1. Example 4 combines new material components with innovative processing techniques, especially hot pressing electromagnetic bending technology. Under the synergistic effect of mold preheating, axial pressure, and alternating magnetic field, the internal organizational structure of the aluminum alloy profile is made more dense and uniform, and the shear strength reaches 320MPa, which is significantly improved compared to Example 1. This shows that the synergy of optimizing material composition and innovative processing technology has a significant effect on improving the shear strength of aluminum alloy profiles.
[0123] In addition, the minimum bending radius reflects the bending performance of aluminum alloy profiles. The smaller the value, the better the forming performance. Figure 3 ) It can be seen that the minimum bending radius of Example 1 is 1.5 times the wall thickness, Example 2 is 1.3 times the wall thickness, Example 3 is 1.0 times the wall thickness, and Example 4 is the smallest, which is 0.8 times the wall thickness. The data shows a progressive change of gradually decreasing;
[0124] The addition of alloying elements such as Zr and Ti improves the comprehensive performance of the alloy and enhances the bending performance to a certain extent. The minimum bending radius of Example 2 is reduced compared with Example 1. Innovative processing techniques such as high-temperature asynchronous rolling and multi-directional forging are used to refine the grains, make the alloy structure more uniform, and further reduce the minimum bending radius. The minimum bending radius of Example 3 is smaller than that of Example 2. Example 4 adopts a hot pressing electromagnetic bending process. Through the synergistic effect of mold preheating, moderate bending rate, axial pressure and dynamically adjusted alternating magnetic field, the forming accuracy and quality of the aluminum alloy profile are greatly improved. The minimum bending radius is reduced to 0.8 times the wall thickness, which is significantly lower than that of Example 1. This fully demonstrates that the synergistic effect of optimizing the composition of aluminum alloy materials and innovative processing techniques can effectively reduce the minimum bending radius of aluminum alloy profiles and improve their bending forming performance.
[0125] All aspects of the present invention are within the scope of protection of this patent.
[0126] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. An aluminum alloy, characterized in that: The material includes the following components by mass percentage: Zn 4.0-5.0%, Mg 1.2-1.8%, Cu 0.1-0.3%, Zr 0.08-0.12%, Ti 0.02-0.06%, Fe ≤ 0.25%, and the balance is Al.
2. A processing technology for aluminum alloy profiles, characterized in that: The following steps are involved: Melting and Casting S1: Alloy elements containing Zn 4.0-5.0%, Mg 1.2-1.8%, Cu 0.1-0.3%, Zr 0.08-0.12%, Ti 0.02-0.06%, and Fe ≤ 0.25% and pure aluminum are added to a melting furnace and melted at 700-750°C to form a melt. An inert gas is introduced or a refining agent is added to refine the melt to remove gas and inclusions. The melt is then transferred to a casting device and cooled at a cooling rate of 5-15°C / s using a semi-continuous or continuous casting method to produce an ingot or billet. High-temperature asynchronous rolling S2: using a differential rolling mill, upper roll speed 20-25rpm, lower roll speed 25-30rpm, and lower roll speed ratio 1:1.0-1.2, rolling temperature 480-500℃, total deformation 60-70%, and multi-directional forging immediately after rolling, strain path change ≥3 times, single deformation 10-15%; Gradient aging treatment S3: The first stage adopts solution treatment at 475℃×1h, water quenching to room temperature, and the second stage adopts double-stage aging at 120℃×8h+180℃×2h, with a heating rate of ≤5℃ / min; Hot pressing electromagnetic bending S4: the mold is preheated to 300-350℃, the bending rate is 1.0-1.2m / min, and the axial pressure of 80-100MPa and the alternating magnetic field of 0.8-1.2T are applied simultaneously. The magnetic field frequency is dynamically adjusted according to f=8×σ, where σ is the real-time compressive stress; Surface treatment S5: Anodizing, electrophoretic coating or powder spraying are performed on the formed profile.
3. The processing technology of the aluminum alloy profile according to claim 2, characterized in that: The core temperature of the rolled plate is fed back in real time through infrared temperature measurement, and the roller speed is dynamically adjusted to make the temperature fluctuation ≤±5°C.
4. The processing technology of the aluminum alloy profile according to claim 2, characterized in that: The bending part is subjected to local micro-arc oxidation treatment, wherein the electrolyte used in the micro-arc oxidation treatment contains 25 g / L Na2Sio3+15 g / L SiC nanoparticles, the voltage is 500 V, and the time is 6-8 minutes.
5. The processing technology of the aluminum alloy profile according to claim 2, characterized in that: In the second stage of the S2 gradient aging treatment, the heating rate from 120°C to 180°C is 3-5°C / min, and a pulsed magnetic field with a frequency of 50 Hz and a magnetic field strength of 0.5-0.8T is applied during the heating process.
6. The processing technology of the aluminum alloy profile according to claim 2, characterized in that: In the multi-directional forging process of S1, the strain path changes 4-6 times, the single deformation is controlled at 12-15%, and the angle between two adjacent forging directions is 90°±5°.
7. The processing technology of aluminum alloy profile according to claim 2, characterized in that: The material is in a dynamic recrystallization temperature window during the bending process, and the product of the bending rate and the axial pressure does not exceed 80% of the yield strength of the material.
8. The processing technology of aluminum alloy profile according to claim 2, characterized in that: The flow rate of the inert gas during the refining process is controlled to be 5-10m 3 / h, refining time is 15-25min.
9. The processing technology of aluminum alloy profile according to claim 2, characterized in that: The rolling force applied to the rolled piece during the rolling process is 1000-1500 kN, and emulsion is used for cooling and lubrication during the rolling process, with the concentration of the emulsion controlled at 3%-5%.
10. The processing technology of aluminum alloy profile according to claim 2, characterized in that: The product model, batch and other identification information are engraved on the surface of the profile. The laser engraving power is 10-20W and the engraving speed is 50-100mm / s.
Citation Information
Patent Citations
Aluminium alloy trough-type part and preparation technology thereof
CN103667820A
Aluminum alloy for making safety components and preparation method thereof
CN104278178A
Al-Zn-Mg alloy and preparation method thereof
CN111254331A
Oversized aluminum alloy plate for aviation container and preparation method of oversized aluminum alloy plate
CN118492291A
Medium-high-strength 7020 aluminum alloy section with complex section and preparation method of medium-high-strength 7020 aluminum alloy section
CN119640107A
Cited By
Aluminum profile and extrusion preparation process thereof
CN121629233A